Unveiling digital creativity: enhancing teachers’ capacities in the digital education landscape - Batuchina, Aleksandra; Melnikova, Julija (Creativity Studies, 2025)
This article aims to unveil the concept of teachers’ digital creativity, recognizing it as one of their fundamental capacities to meet the challenges posed by digital education. The theoretical segment of the article engages in a comprehensive discourse on the concept of teachers’ digital creativity. The theoretical discourse is complemented by an empirical study, engaging general education school teachers, to provide insights into their understandings and perspectives related to digital creativity. The empirical study was organized in Lithuanian general educations schools. Eleven interviews with teachers, who are already using digital tools and platforms in their teaching process, were conducted. The research findings not only enrich the understanding of teachers’ digital creativity in education, but also lay the groundwork for the further development of a robust framework of teachers’ digital creativity, offering practical considerations that may be essential for its effective formulation and implementation.